Protoplast isolation from Solanum lycopersicum L. leaf tissues and their response to short-term NaCl treatment - Horváth, Edit (Acta Biologica Szegediensis, 2009)
Protoplasts were isolated from young leaves of tomato (Solanum lycopersicon L. cvar Rio Fuego). The optimum conditions for protoplast isolation was established by using 2% cellulose R-10 and 0.5% macerozyme R-10 dissolved in 0.4 M sucrose-K3 solution for 12 h cell wall digestion. In order to induce salt stress, the mannitol content of the buffer was partially replaced by NaCl to get an isoosmotic incubation solution containing 100 mM NaCl. It can be concluded that the number of protoplast in unit volume counted by Bürker chamber did not decrease significantly compared to controls due to salt treatment upto 5 hours, but the viability of cells decreased by 55% using fluorescein diacetate staining. Hundred mM NaCl simultaneously enhanced the generation of reactive oxygen species in tomato leaf protoplast. This means that decreases in fluorescein fluorescence is a good and sensitive parameter for the measurement of Na+-induced decrease in cell viability and cell death in protoplast suspensions.